Experimental and Analytical Study of the Energy Spectrum and Decay Schemes of both Isotopes Cobalt (_27^60)Co and Sodium (_11^22)Na (Latakia University Journal -Basic Sciences Series, 2021)
In this work, we have used the basic techniques for measuring the gamma rays by using a sodium iodide detector that is thallium activated ( ) to study the decay schemes and the energy spectrum of cobalt  and sodium  isotopes.We have obtained in this work:• The detector calibration and the resolution of a spectrometer.• The spectrum of cobalt  and sodium  isotopes.• The experimental and analytical study of the decay schemes and the energy spectrum of both isotopes Cobalt  and Sodium• The comparison of energy lines of the energy spectrum with exited states of the exited nucleus  and  produced from cobalt  and sodium . Comparing the results obtained with the results available in this field, indicates a very good agreement.